Determinant Variables of MSMEs’ Digital Transformation In Pharmacies In Indonesia during the COVID-19 Pandemic - Lawita, Florencia Irena; Iskandar, Donant Alananto; Adrian, Michael (TOPAZART, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy. According to several definitions, pharmacies can be counted as Medium Enterprises. However, the COVID-19 Pandemic dealt a blow to the world’s economy which resulted in many MSMEs being forced to close. MSMEs had to adapt using various ways in order to survive. One of the possible ways to adapt is by adopting a Business Model Innovation that integrates Digitalization, in other words, part of the business is done online. This research aims to see whether pharmacies in DKI Jakarta, the City of Tangerang and the City of South Tangerang have already implemented Digitalization by collaborating with the Halodoc application. This research also will see what are the motivations for Digitalization and whether it has had a positive impact for the pharmacies in terms of the sales of products. Furthermore, this research also will investigate the influence of Interprofessional Collaboration, Green Economy and Responsibility to the Government on Digital Transformation. Data will be collected quantitatively, and quantitative data will be processed by way of descriptive statistics using the program SPSS 22nd Version. The results of the research can be used by the Government and related institutions to craft policies that can encourage the Digitalization of MSMEs in Indonesia in order to reach the Sustainable Development Goals in the effort to develop a Green Economy.